THE USE OF DIGITAL VLOG MEDIA TO IMPROVE SPEAKING SKILLS - Mardhyanti, Mardhyanti; Sulistyo, Teguh; Andy, Andy (KLAUSA (Kajian Linguistik, Pembelajaran Bahasa, dan Sastra), 2023)
The rapid development of digital technology today requires all parties to participate in developing themselves and following the flow by utilizing the results of technology in all activities. The impact of this technological development also impacts the learning process in schools, where the educators must be able to carry out various innovations and creativity so that the learning process is always relevant to the existing developments. One of the innovations and creative things that educators can do is use digital technology as a learning medium. Learning media in the form of digital technology can be a special attraction for providing enthusiasm for learning to students. One of the results of the development of digital technology that can be used as a fun learning medium is a video blog, or Vlog. A vlog is a video and web-based communication and information medium that combines creativity, information, and entertainment in one work. This paper tries to reveal how Vlogs can be used as an effective and fun learning medium to increase students' interest in learning. By mastering digital technology and implementing it through fun learning media, it is expected to improve the quality of learning. The implications of the research are also discussed.